MISI EMANSIPATORIS PENYELENGGARAAN PENDIDIKAN ISLAM - Zuhriyah, Indah Aminatuz (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
In facing the complexity of life, the process and the education system are not free from some problems such as political problem, economic problem social problem, cultural problem, and religious problem. The choices of functions which are given priority depend on the outcome of the interaction process and the education system with its environment. Facing the reality, the important thing to notice is to restore the initial orientation of the Islamic education itself, namely by providing emancipatory liberation or a mission for every human being. So with the education, people are able to realize the ideal of the Islamic education namely being a man of Muslim plenary.